Oncogenic stress induced by acute hyper-activation of Bcr-Abl leads to cell death upon induction of excessive aerobic glycolysis. - Michael A Dengler (Public Library of Science (PLoS), 2011)
In response to deregulated oncogene activation, mammalian cells activate disposal programs such as programmed cell death. To investigate the mechanisms behind this oncogenic stress response we used Bcr-Abl over-expressing cells cultivated in presence of imatinib. Imatinib deprivation led to rapid induction of Bcr-Abl activity and over-stimulation of PI3K/Akt-, Ras/MAPK-, and JAK/STAT pathways. This resulted in a delayed necrosis-like cell death starting not before 48 hours after imatinib withdrawal. Cell death was preceded by enhanced glycolysis, glutaminolysis, and amino acid metabolism leading to elevated ATP and protein levels. This enhanced metabolism could be linked to induction of cell death as inhibition of glycolysis or glutaminolysis was sufficient to sustain cell viability. Therefore, these data provide first evidence that metabolic changes induced by Bcr-Abl hyper-activation are important mediators of oncogenic stress-induced cell death.During the first 30 hours after imatinib deprivation, Bcr-Abl hyper-activation did not affect proliferation but resulted in cellular swelling, vacuolization, and induction of eIF2α phosphorylation, CHOP expression, as well as alternative splicing of XPB, indicating endoplasmic reticulum stress response. Cell death was dependent on p38 and RIP1 signaling, whereas classical death effectors of ER stress, namely CHOP-BIM were antagonized by concomitant up-regulation of Bcl-xL.Screening of 1,120 compounds for their potential effects on oncogenic stress-induced cell death uncovered that corticosteroids antagonize cell death upon Bcr-Abl hyper-activation by normalizing cellular metabolism. This protective effect is further demonstrated by the finding that corticosteroids rendered lymphocytes permissive to the transforming activity of Bcr-Abl. As corticosteroids are used together with imatinib for treatment of Bcr-Abl positive acute lymphoblastic leukemia these data could have important implications for the design of combination therapy protocols.In conclusion, excessive induction of Warburg type metabolic alterations can cause cell death. Our data indicate that these metabolic changes are major mediators of oncogenic stress induced by Bcr-Abl.